If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4x+2(x+3)=2(x+2)
We move all terms to the left:
4x+2(x+3)-(2(x+2))=0
We multiply parentheses
4x+2x-(2(x+2))+6=0
We calculate terms in parentheses: -(2(x+2)), so:We add all the numbers together, and all the variables
2(x+2)
We multiply parentheses
2x+4
Back to the equation:
-(2x+4)
6x-(2x+4)+6=0
We get rid of parentheses
6x-2x-4+6=0
We add all the numbers together, and all the variables
4x+2=0
We move all terms containing x to the left, all other terms to the right
4x=-2
x=-2/4
x=-1/2
| (5v^2)+10v+33=-5 | | 9x-6*3x+81=0 | | |z+59|=|z−79| | | 2+(x(x))-(-2x)=x-2-(-x(-x)) | | 5x+3=√125 | | x+.2x=100000 | | 11.74-14.5h=-13.7h+19.18 | | -3=5-1b | | -12-4+7.5c-11=-6 | | 11.74-15.5h=-13 | | 495=x+2*x*5 | | 9x-6)=(8.5x+2 | | -7+4(-9x+3)=-10 | | 0.3d+7.9=9.1 | | 2p-12=8p-12 | | 15.25+19.5t=13.4t | | 5/2x+1/2=21/2+7/2x | | 4v-2=2v-2+(v+100/4) | | 2/5x-10=18 | | 114-u=234 | | y=10(3-8) | | 9=32-x | | -3+3y=-19+11y | | x+3-(-2x)=-2+x-(-2x+x) | | -6m+12-3=9-6m | | 4(-2x+3)=-10x+6 | | 6p+2=4p-1 | | 5x-35=2x+5 | | x=32-9 | | x+0.2x=25.44 | | x=32+9 | | 30+6p=12+12p |